Hubungan Efikasi Diri dan Pengetahuan dengan Kecemasan Mahasiswa dalam Praktik Klinik Keperawatan - Suriansyah Marhamad; M. Abrar Parinduri; Nur’aini Nur’aini (Mahesa Research Center, 2022)
This study aims to determine the relationship between self-efficacy and knowledge with student anxiety in nursing clinical practice. This research is a quantitative descriptive study with a correlational approach, the data was collected using a questionnaire method. The research sample was taken with a total sampling of 67 students who carried out nursing clinical practice. The results of data analysis showed that there was a very significant negative relationship on self-efficacy with anxiety, which was indicated by the correlation coefficient rX1Y = - 0.655 with p < 0.01. This means that the better the self-efficacy, the lower the anxiety experienced. Furthermore, there is a very significant negative relationship between knowledge and anxiety, which is indicated by the correlation coefficient rX2Y = - 0.674 with p < 0.01. This means that the more knowledge students have, the less anxiety they experience. There is a relationship between self-efficacy and knowledge with anxiety, which is indicated by the coefficient F = 32.646 with p < 0.01. The magnitude of the correlation is r = 0.711 with R2 = 0.505, this means that together self-efficacy and knowledge contribute to the emergence of anxiety by 50.5% and there is 49.5% anxiety experienced by nursing students is influenced by other factors. By assuming knowledge is in a constant condition, every increase of 1 unit of self-efficacy variable will reduce the level of anxiety experienced by students by 0.375, and vice versa by assuming self-efficacy in constant conditions, every increase of 1 unit of knowledge variable will reduce student anxiety level by 1,996.